Foxg1 Antagonizes Neocortical Stem Cell Progression to Astrogenesis. (1st March 2019) - Falcone, Carmen; Santo, Manuela; Liuzzi, Gabriele; Cannizzaro, Noemi; Grudina, Clara; Valencic, Erica; Peruzzotti-Jametti, Luca; Pluchino, Stefano; Mallamaci, Antonello
Abstract: Neocortical astrogenesis follows neuronogenesis and precedes oligogenesis. Among key factors dictating its temporal articulation, there are progression rates of pallial stem cells (SCs) towards astroglial lineages as well as activation rates of astrocyte differentiation programs in response to extrinsic gliogenic cues. In this study, we showed that high Foxg1 SC expression antagonizes astrocyte generation, while stimulating SC self-renewal and committing SCs to neuronogenesis. We found that mechanisms underlying this activity are mainly cell autonomous and highly pleiotropic. They include a concerted downregulation of 4 key effectors channeling neural SCs to astroglial fates, as well as defective activation of core molecular machineries implementing astroglial differentiation programs. Next, we found that SC Foxg1 levels specifically decline during the neuronogenic-to-gliogenic transition, pointing to a pivotal Foxg1 role in temporal modulation of astrogenesis. Finally, we showed that Foxg1 inhibits astrogenesis from human neocortical precursors, suggesting that this is an evolutionarily ancient trait.